Tanggung Jawab Kantor Pertanahan terhadap Terbitnya Sertifikat Ganda (Studi Kasus Putusan Kasasi MA No. 162 K/TUN/2012) - zuman malaka (Al-Qanun: Jurnal Pemikiran dan Pembaharuan Hukum Islam, 2017)
This paper will examine and analyze the legal responsibilities of the Land Office, with a focus on case studies on Supreme Court Decisions. 162 K/ TUN/2012. At the end of this paper, it is concluded that: (1) the existence of this decision indicates that the settlement of land disputes can be through the media of the Adminsitration Court, (2) the content of a decision in the form of a command to the Head of the Land Office of Kendari to revoke and cross out from the land book is the responsibility of the institutional (3) if maladministration is found, personal criminal liability may be filed, and (3) as well as if there is a loss to the plaintiff it can be filed a lawsuit civil to the Official, whose responsibilities may be institutional or personal, with regard to whether or not maladminsitration exists.